An analysis on the persuasive elements in the Malaysian Public Universities digital promotional materials / Nor Atifah Mohammad, Ameiruel Azwan Ab Aziz and Nazarul Azali Razali - Mohammad, Nor Atifah; Ab Aziz, Ameiruel Azwan; Razali, Nazarul Azali (Akademi Pengajian Bahasa, 2021)
University digital promotional materials act as a communication tool between the university and prospective students. The materials are crucial to entice prospective students and thus employing the persuasive elements are much needed to attract the attention. Nevertheless, there is a breach in the existing literature in which little research has focused on persuasive discourse in Malaysian universities’ promotional materials. The proposed study intends to examine further and understand the different extent of the combination of textual and visual elements used in the digital promotional materials to achieve its persuasive function in the Malaysian public universities’ digital promotional materials. This study will focus on all twenty Malaysian public universities’ digital promotional materials embedded in their admission tab. Content analysis will be used to analyse the persuasive elements. All data will be coded and categorised, and emergent themes will be presented to answer research questions. With great hope, the results of this study can provide further recommendations for interventions from universities’ website and content developers to improve the linguistics presentations to attract larger student enrollment.